‘A Tragedie Written in Greeke’: How Jocasta was Made ‘Classical’ - Bigliazzi, Silvia (Early Theatre)

(untitled) (McMaster University Library Press / Becker Associates, 2024)
Critics often take for granted that Dolce’s Italian translation of a Latin version of Euripides’s Phoenician Women provided Gascoigne and Kinwelmersh with a ready example for composing a ‘classical’ drama for an English Renaissance audience. However, the choice of an Italian play with a Greek story for the performance of the first Greek tragedy in England at Gray’s Inn in 1566 remains a sidelined question. This article argues that one reason for their choice of Dolce’s play resides in his treatment of the Euripidean material in ways that attuned it to contemporary dramaturgical as well as cultural and political circumstances while scattering signposts throughout, suggesting belongingness to classical antiquity. One of these features was the female lament shared by the chorus and Antigone in the last act, which, while absent from Euripides, was a model that could be recognized as Euripidean and, more broadly, Greek.